2008
DOI: 10.1080/01674820701690624
|View full text |Cite
|
Sign up to set email alerts
|

Types, patterns, and predictors of coping with stress during pregnancy: Examination of the Revised Prenatal Coping Inventory in a diverse sample

Abstract: The present study investigated coping in early, mid-, and late pregnancy in 321 ethnically and socioeconomically diverse women of varying medical risk. The goal was to determine how women cope with stress across pregnancy and to explore the association of coping with maternal characteristics, stress perceptions, disposition, and social support. Factor analysis of the Revised Prenatal Coping Inventory revealed three distinct types of coping: Planning-Preparation, Avoidance, and Spiritual-Positive Coping. Spirit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 33 publications
10
117
1
9
Order By: Relevance
“…Hamilton JG and Lobel M (2008) added new items to the original PCI and developed a 42-item measure. In the Nu-PCI, respondents report how often they used different coping mechanisms in the past month on a range from 0 to 4 (0, never; 1, almost never; 2, sometimes; 3, fairly often; 4, very often).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamilton JG and Lobel M (2008) added new items to the original PCI and developed a 42-item measure. In the Nu-PCI, respondents report how often they used different coping mechanisms in the past month on a range from 0 to 4 (0, never; 1, almost never; 2, sometimes; 3, fairly often; 4, very often).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the Persian Nu-PCI domains indicated the ability to correlate with the WCQ domains, indicating a satisfactory convergent validity of the instrument. As with Yali AM and Lobel M (2002) and Hamilton JG and Lobel M (2008), strong correlations in the domain scores of the Nu-PCI showed a sufficient concurrent validity [22,24]. The WCQ, a similar instrument that is widely used in psychological research, showed a valid scale of coping strategies [27,28], and there were acceptable reliability coefficients and correlations with related constructs in items of the questionnaire [12,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies point to inadequate awareness of women who are offered individual methods of screening [1][2][3][4][5] . These authors concentrated particularly on stress, coping strategies and provision of support for pregnant women in connection with invasive screening tests [6][7][8][9][10] . More studies are discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…Avoid: Women can discard physical changes during pregnancy and try to hide their feelings about pregnancy. [11,12] A Proper coping mechanism for stress is essential for pregnant women to protect maternal and fetal health.…”
Section: [1]mentioning
confidence: 99%